2004
DOI: 10.1002/nau.20088
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ regulation in a human prostate stromal cell culture

Abstract: PrS6 prostate stromal cells express functional alpha1-adrenoceptors associated with spontaneous intracellular Ca2+-transients. They exhibit functional Ca2+ channels, intracellular Ca2+ stores, and Ca2+ entry induced by store depletion. Stromal cultures can therefore be used to characterize the cellular physiology of prostate stromal cell contraction and proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
3
4
0
Order By: Relevance
“…68 Later studies showed that human cultured prostatic stromal cells also responded to phenylephrine with elevations of intracellular inositol trisphosphate, protein kinase C translocation and Ca 2+ entry, 92 the Ca 2+ elevation being sensitive to protein kinase C blockers 92 and the L-type Ca 2+ channel blocker nifedipine. 92,93 The ␣1-adrenoceptor-operated mechanisms underlying these effects in human cultured prostatic stromal cells are generally consistent with the mechanism proposed by Eckert et al 13 to describe phenylephrine-induced Ca 2+ entry into acutely dispersed prostatic smooth muscle. Their proposal was that ␣1-adrenoceptor activation stimulated the production of inositol trisphosphate, subsequent release of Ca 2+ from intracellular stores and opening of L-type Ca 2+ channels via Ca 2+ -calmodulin.…”
Section: Cultured Cell Models Of Human Prostate Contractilitysupporting
confidence: 77%
“…68 Later studies showed that human cultured prostatic stromal cells also responded to phenylephrine with elevations of intracellular inositol trisphosphate, protein kinase C translocation and Ca 2+ entry, 92 the Ca 2+ elevation being sensitive to protein kinase C blockers 92 and the L-type Ca 2+ channel blocker nifedipine. 92,93 The ␣1-adrenoceptor-operated mechanisms underlying these effects in human cultured prostatic stromal cells are generally consistent with the mechanism proposed by Eckert et al 13 to describe phenylephrine-induced Ca 2+ entry into acutely dispersed prostatic smooth muscle. Their proposal was that ␣1-adrenoceptor activation stimulated the production of inositol trisphosphate, subsequent release of Ca 2+ from intracellular stores and opening of L-type Ca 2+ channels via Ca 2+ -calmodulin.…”
Section: Cultured Cell Models Of Human Prostate Contractilitysupporting
confidence: 77%
“…Spontaneous elevations of calcium and spontaneous contractions have been shown previously in HCPSC 15,16. Although Boesch et al 16 report that the number of cells exhibiting spontaneous contractions is significantly elevated by the α‐adrenoceptor agonist phenylephrine, in our studies the non‐selective adrenoceptor agonist, noradrenaline, had no effect on peaking activity.…”
Section: Discussionsupporting
confidence: 53%
“…Levels of [Ca 2+ ] i in HCPSC have been found to be regulated by α‐adrenoceptors which cause influx of calcium through L ‐type channels and release of calcium from intracellular stores 6,8,15. We therefore investigated the effects of testosterone on the ability of the adrenoceptor agonist, noradrenaline, to regulate [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…Sixtyseven percent of cells showed a biphasic response suggesting that PE stimulation is coupled to an intracellular pool of Ca 2þ . The PE-induced [Ca 2þ ] i increase reported here is in agreement with the previous study from Eckert et al [1995] and from Wu et al [2005] demonstrating a similar adrenergic Fig. 6.…”
Section: Discussionsupporting
confidence: 95%